2019
DOI: 10.1136/bmjoq-2018-000402
|View full text |Cite
|
Sign up to set email alerts
|

Financial incentives linked to quality improvement projects in Swedish primary care: a model for improving quality of care

Abstract: BackgroundQuality improvement (QI) is necessary in all healthcare, but quality of healthcare is hard to measure. To use financial incentives to improve care is difficult and may even be harmful. However, conducting QI projects is a well-established way to increase quality in healthcare.ProblemIn 2015, there were few QI projects conducted in primary care in the Stockholm Region, Sweden. There was no structured support or way to share the QI projects with other general practitioner (GP) practices. To use financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In fact, a recent study from the UK reported that only 20% of GPs and 33% of practice managers knew about the PDSA model [ 62 ]. Financial incentives for using PDSA in QI in Swedish PC have been tested [ 63 ] but the impact on the care provided is yet to be studied. Although they accepted the need for external support, the participants in our study stressed the need to adapt the methods of QI to their own needs and capabilities, and to focus on results rather than strict compliance with methods.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a recent study from the UK reported that only 20% of GPs and 33% of practice managers knew about the PDSA model [ 62 ]. Financial incentives for using PDSA in QI in Swedish PC have been tested [ 63 ] but the impact on the care provided is yet to be studied. Although they accepted the need for external support, the participants in our study stressed the need to adapt the methods of QI to their own needs and capabilities, and to focus on results rather than strict compliance with methods.…”
Section: Discussionmentioning
confidence: 99%
“…immunisation) and non-financial incentives (i.e. continuing professional development -CPD points) to promote the recording and monitoring of medicinal cannabis prescribing by GPs (Fernholm et al 2019;Hallinan 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This has implications for our findings which suggest a preference for a localised approach to QI. A study in Sweden in which Stockholm general practices were financially incentivised to carry out QI projects, found that the number of QI projects reported more than doubled compared with the year before the intervention 23. It seems likely that this was due to the financial incentivisation, although in the absence of a control group it is not possible to attribute the outcome to the intervention with confidence.…”
Section: Discussionmentioning
confidence: 99%